EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERN PERSEDIAAN BARANG DAGANGAN PADA TOKO MAHKOTA DIESEL MANADO - Samuna, Juwita Natalia; Sabijono, Harijanto; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2017)
Internal control system is a way or system that can prevent the occurrence of irregularities in the company. Internal control system of the inventory aims to protect the company's assets from theft. The research object is taken at the Manado Diesel Crown Store is one of the stores in Manado that runs the business by selling machines and spare parts. This study aims to evaluate the effectiveness of the application of internal control system merchandise inventory at Diesel Manado.The method of analysis used in this research is descriptive qualitative analysis method. Based on the results of internal control inventory of merchandise inventory at Manado Diesel Crown Store, then in the control environment that occurs in the company, there is a double position between the sales and the warehouse. In the accounting system, the documents used are not serial number printed. In control procedures, authorization system is only on certain transactions.Keywords: internal control system, merchandise inventory